2022
DOI: 10.1039/d2ta00884j
|View full text |Cite
|
Sign up to set email alerts
|

Vicinal Co atom-coordinated Fe–N–C catalysts to boost the oxygen reduction reaction

Abstract: Fe-N-C catalysts have been achieved great progresses in catalytic activity for oxygen reduction reaction (ORR) in acid, whereas the unsatisfactory durability has not been improved yet. Here, we rationally introduce...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…S5†). 46,47 The excellent electrocatalytic performance may be due to more defects caused by the doping of Co species, which is conducive to the subsequent generation of more Fe–N 4 species by Fe adsorption. Meanwhile, the porous structure helps to increase the specific surface area and promote the exposure of the active sites.…”
Section: Resultsmentioning
confidence: 99%
“…S5†). 46,47 The excellent electrocatalytic performance may be due to more defects caused by the doping of Co species, which is conducive to the subsequent generation of more Fe–N 4 species by Fe adsorption. Meanwhile, the porous structure helps to increase the specific surface area and promote the exposure of the active sites.…”
Section: Resultsmentioning
confidence: 99%
“…FeCoN x /C reached an extraordinary E 1/2 of 0.86 V in 0.1 M HClO 4 , and this performance exceeds the current state-of-the-art non-precious metal catalysts, which can be attributed to the extremely high intrinsic activity of the FeCoN 5 –OH site. Chen et al 113 then proposed the doping of Co atoms in the Fe–N–C catalyst (FeCo–NC-3), which not only boosts the catalytic activity, but also improves the stability of the catalysts. The HAADF-STEM and FT-EXAFS together proved the existence of Fe–Co binuclear sites, and the fitting Fe K-edge EXAFS confirmed that the coordination numbers of Fe–N and Co–N are both close to 4, so the most likely structure of active sites is shown in Fig.…”
Section: Dual Metals As Catalytically Active Site Centersmentioning
confidence: 99%
“…the two metals greatly enhance the stability compared with the SACs. [79][80][81] For example, Li and co-workers [82] constructed one of Fe-Co DACs [83][84][85][86][87] on N-doped porous carbon (NC) by a host-guest strategy, which showed higher selectivity of accelerating the four-electron reduction process than SACs for ORR in acid medium. There are many similar studies about the DACs promote ORR reported so far, including Zn/Co, [88] Fe/ Zn, [89] FeNi, [90] FeMn, [91] CoNi.…”
Section: Introductionmentioning
confidence: 99%